Theoretical Approach to the Management of Epidural Hematoma (EDH): Optimal Timing for Surgical Intervention - Hafzul; Ahmad, Diwa Aulia (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2025)
Introduction: Epidural hematoma (EDH) is a life-threatening condition that requires timely surgical intervention to prevent irreversible neurological damage, with early decompression within the "golden hour" being critical for better outcomes. Case Description: Two cases were discussed: Case 1, an 81-year-old female who underwent surgery within 12 hours with significant recovery, and Case 2, a 73-year-old male who showed deterioration after delayed intervention but improved following decompression within 12 hours. Discussion: Early surgical intervention prevents brain herniation and secondary brain injury. The "golden hour" concept emphasizes decompression within hours of symptom onset. Access to timely care in rural settings can delay intervention, worsening outcomes. The timing of surgery must consider individual patient factors, such as comorbidities and hematoma size. Conclusion: Optimal surgical timing, especially within the "golden hour," is critical in EDH management to prevent irreversible neurological damage. Individualized treatment plans should account for access to care and patient-specific factors for the best outcomes.